Effects of moxibustion on reproduction and metabolism of polycystic ovary syndrome: a protocol for meta-analysis and systematic review - Wei Huang; Zhongyu Zhou; Kou Xu; Jiajie Wang; Feng Hu; Siying Lv; Yanji Zhang; Qiqi Yang (BMJ Open)
Introduction Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathy in women of reproductive age. Recently, moxibustion, as a complementary and alternative therapy, has been commonly used in assisted reproduction and improvement of metabolic abnormalities in patients with PCOS. Currently, intervention efficacy of the use of moxibustion in PCOS treatment still remains controversial due to lack of high-quality evidence. Consequently, this study protocol was designed to objectively review and evaluate the effectiveness and safety of moxibustion treatment for PCOS.Methods and analysis Electronic searches will be carried out from inception to May 2021 in the online databases of The Cochrane Library, PubMed, EMBASE, Chinese Biomedical Literature, Chongqing VIP Chinese Science and Technology Periodical Database (VIP) and China National Knowledge Infrastructure. The Chinese Clinical Trial Registry Center and Clinical Trials will be used for searching ongoing trials. Randomised controlled trials and the first period in randomised cross-over trials involving any type of moxibustion for patients with PCOS will be included. Primary outcomes will be the ovulation rate, pregnancy rate and sex hormone levels, and secondary outcomes will be changes in clinical symptoms and metabolic indicators, total effective rate and the incidences of side effects and adverse events. Briefly, two reviewers will independently conduct study selection and data extraction, and the risk of bias will be assessed. Prior to the formal meta-analysis, the heterogeneity of included studies will be assessed. Review Manager Statistical Software (RevMan) V.5.3 will be used for data processing. Finally, the Grading of Recommendations Assessment, Development and Evaluation method will be applied to evaluate the quality of evidence.Ethics and dissemination Ethical approval is not necessary since this study is designed as a systematic review. This study will be disseminated by a peer-review journal or conference presentation.